2023
DOI: 10.1001/jamanetworkopen.2023.3660
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery, Symptoms, and Quality of Life 1 to 5 Years After Traumatic Brain Injury

Abstract: ImportanceMany level I trauma center patients experience clinical sequelae at 1 year following traumatic brain injury (TBI). Longer-term outcome data are needed to develop better monitoring and rehabilitation services.ObjectiveTo examine functional recovery, TBI-related symptoms, and quality of life from 1 to 5 years postinjury.Design, Setting, and ParticipantsThis cohort study enrolled trauma patients across 18 US level I trauma centers between 2014 and 2018. Eligible participants were enrolled within 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 52 publications
2
10
0
1
Order By: Relevance
“…TBI patients experience numerous affective, cognitive, and physical symptoms even a year post-injury, and nurses should monitor for adverse effects and symptoms. Our study confirms a recent study (Transforming Research and Clinical Knowledge in Traumatic Brain Injury, or TRACK-TBI) (Nelson et al, 2023) that symptoms significantly impact patient functioning. Studies of symptoms in TBI typically focus on the first few weeks postinjury (e.g., Brett et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…TBI patients experience numerous affective, cognitive, and physical symptoms even a year post-injury, and nurses should monitor for adverse effects and symptoms. Our study confirms a recent study (Transforming Research and Clinical Knowledge in Traumatic Brain Injury, or TRACK-TBI) (Nelson et al, 2023) that symptoms significantly impact patient functioning. Studies of symptoms in TBI typically focus on the first few weeks postinjury (e.g., Brett et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Initial severities of TBI often determine the procedures for acute triage and care. However, severities of TBI begin to intersect after several months to years, with an example of some moderate TBI patients can recover quickly ( 68 ), whereas ( 68 ), whereas mild TBI does not mean patients recover patients recover rapidly, in fact some patients can develop lingering symptoms, whereas mild TBI does not mean patients recover rapidly, in fact some patients can develop lingering symptoms for months to years ( 69 ). Therefore, initial severities of TBI in the selected RCTs may be less relevant when interpreting the effectiveness of interventions for chronic TBI cases.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing appreciation that mTBI can be linked to long-term consequences. For example, Nelson et al ( 3 ) reported that 53% of mTBI patients evaluated at U.S. Level 1 trauma center emergency departments (EDs) report injury-related functional impairments 1-year post-injury. Functional impairments can have a direct impact on life quality and satisfaction and are often linked to persistent injury-related symptoms, such as psychological distress ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%